The Manifestation of Kuntisraya Story in Ethnic - Dyah Kustiyanti; Suminto Suminto; I Wayan Sutirtha (RIRAI Publisher, 2023)
The purpose of writing this article is to discover the manifestations of the Kuntisraya story in works of arts in Indonesia. In general, Kuntisraya stories can be found in ancient Javanese literary works. In particular, it turns out that there are works of art, design, and ethnic performing arts in Indonesia that are realized based on the Kuntisraya story. The problems are : 1) What is the form of the manifestation of the Kuntisraya story in works of art and design?; 2) What is the form of the manifestation of the Kuntisraya story in ethnic performing arts?. This research was conducted with qualitative methods. Observations and interviews have been used to obtain primary data. The results of the literature study have been used as secondary data. All data has been analyzed qualitatively using aesthetic and reception theories. The results of the study show that : 1) manifestations of the Kuntisraya story exist in works of art and designs in the form of architectural reliefs of temples; and 2) manifestations of the Kuntisraya story exist in performing arts in the form of sacred performing arts and tourism performing arts.